Analisis Dampak Pertambangan terhadap Ekonomi dan Lingkungan di Provinsi Papua : (Studi Kasus PT Freeport Indonesia) - Restuning Amalia (Journal of Economics Development Issues, 2023)
The mining and quarrying activities carried out by PT Freeport Indonesia in Papua Province greatly affect the economic and environmental aspects. This study aims to analyze the economic impact, especially GRDP, and the environment caused by PT Freeport. The research methodology in this study uses quantitative analysis where the data obtained are sourced from the Central Statistics Agency. The results of this study indicate that the mining and quarrying sector has the highest contribution compared to other sectors as evidenced by the average contribution rate in 2017-2021 of 37.38%. On the environmental aspect, the presence of PT Freeport causes environmental damage as evidenced by the accumulation of tailings containing acid rock water.